Profil keterampilan menguasai ritme dasar dalam pembelajaran seni musik siswa kelas IV sekolah dasar - Aljazira Yasyirulgaza Intifada; Karsono Karsono Karsono (Didaktika Dwija Indria, 2025)
This study aimed to describe the profile of basic rhythm skills of class IV students in musical arts learning in Laweyan District, Surakarta, academic year 2024/2025. The study used a quantitative approach with a sample of 92 students from five elementary schools selected using the Slovin formula. Data were collected through skills and documentation tests, with indicators including imitation rhythm, reading rhythm, and rhythm identification. Data analysis was performed using descriptive statistics with the help of Microsoft Excel and SPSS. The results showed that the mean of the students' basic rhythm skills was 81.9, in the "very high" category. In the rhythm imitation facet, the mean reached 85.2 (very high category), rhythm reading 71.5 (high category), and rhythm identification 80.6 (very high category). The use of digital media such as the Musescore app has been shown to be effective in increasing students’ interest and understanding of basic rhythms. These results highlight the importance of a balance between theory and practice in teaching musical arts to maximize students’ skills. This research contributes to providing an overview of students’ basic rhythm skills and serves as a basis for further development in learning musical arts. The implementation of digital media and concrete methods can improve the quality of learning and help students understand the concept of rhythm deeply.